The way it's written, k = 7, and since 3(-k-4)+6 = k = 7, then 3(-k-4)+6 = 7, as well. Sub 7 for k and let's see if this is solvable. 3(-7-4)+6 = 3(-11) + 6 = -33 + 6 = -27. Obviously, -27 is not equal to 7, so either the problem is unsolvable or there's a typo somewhere.

If the second "=" is supposed to be a "+," then you would solve it like so:

3(-k-4) + 6 = k +7. Subtract K from both sides so all the unknowns are on the left, like so: 3(-k-4) + 6 - k = k - k +7. 3(-k-4) + 6 - k = 7. Parentheses come first, so the next step would be: -3k -12 + 6 - k = 7. Reorganize the problem with the k's together to make ti easier to read (and since order of operations is no longer important) -3k - k - 12 + 6 = 7. Get the k's together and add -12 + 6: -4k - 6 = 7. Add 6 to both sides: -4k - 6 + 6 = 7 + 6. -4k = 13. add 4k to each side and subtract 13 from each side so teh -4k becomes 4k, like so: -4k + 4k - 13 = 13 - 13 + 4k. -13 = 4k. Reverse so the 4k is on the left: 4k = -13. Divide both sides by 4: 4k/4 = -13/4. 4 = -13/4 = -3 1/4 = -3.25.

If the second "=" was supposed to be a "-" sign: 3(-k-4)+ 6 = k - 7. Do the same steps as last time:

-3k - 12 + 6 = k -7. -3k + - k - 6 = k - k - 7. -4k - 6 = -7. -4k + 4k - 6 + 7 = - 7 + 7 + 4k. 1 = 4k. 4k = 1. k = 1/4, or 0.25

## Comments

Is the equation supposed to be 3(-k-4)+6=k+7 or 3(-k-4)+6+k=7? It doesn't make sense with two equal signs.